Polycystic ovary syndrome and circulating inflammatory markers - Farideh Zafari Zangeneh; Mohammad Mehdi Naghizadeh; Masoumeh Masoumi (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Human and experimental studies suggest that the sympathetic regulatory drive in the ovary may be unbalanced (hyperactivity) in polycystic ovary syndrome (PCOS). Dysfunctional secretion of interleukin (IL) -1 (α & β) or related cytokines may thus be related to abnormal ovulation and luteinization. Objective: The aim of this study was the evaluation of cytokines’ pattern in PCOS women and discussion about the explanation of cross-talk between two super systems: sympathetic and immune systems and explanation sympatho-excitation and relationship with interleukins. Materials and Methods: In this study, 171 PCOS women aged between 20-40 years were studied. Their body mass index was <28. The patients were divided into two groups: study group (n=85, PCOS women) and control group (n=86 normal women). The blood sample was obtained on the 3rd day of menstruation cycle. IL-17, IL-1α, IL-1β, and Tumor necrosis factor-alpha (TNF-α) concentrations were determined in both groups. Results: The median serum level of IL-1α in the PCOS group was higher than the control group (293.3 and 8.0, respectively, p<0.001). Also, the median serum level of IL-1β was higher than the control group (5.9 and 3.1 respectively). But the median serum of level IL-17 in women with PCOS was significantly lower than the control group (p<0.001). Conclusion: Our results confirm that PCOS is a low-level chronic inflammation